Illocutionary Acts Found in Novel the Never Girls: Before the Bell by Kiki Thorpe - Dolla Vania Petriandy; Leni Marlina (English Language and Literature, 2018)
The purpose of this paper is to analyze types of illocutionary act found in novel The Never Girls Bell: Before the Bell by Kiki Thorpe. This research used the descriptive qualitative method. The data of this research is the utterances of novel The Never Girls Bell: Before the Bell by Kiki Thorpe published in 2016. The data is taken from chapter one, page one until seven. This data would be analyzed based on Searle’s theory about classifications of illocutionary act. There are some types of illocutionary act in this paper; they are representative (informing, asserting, predicting, reporting); directive (asking, requesting, stating), commisive (promising); expressive (liking, complimenting), and declarative. The finding of the data has shown that in novel the highest is representative 28 data or about 50% and the highest representative type is informing. And the second is directive 21 data or about 37, 5% and the highest directive is asking. From the result of the study that the dominant type of illocutionary act is representative and the dominant sub-type of representative is informing.